Quo Vadis, Random Graph Theory? - Palmer, Edgar M. (Annals of Discrete Mathematics, 1993)
We trace the growth of the random graph theory from its inception with the fundamental papers of Erdős and Rényi in 1959-60 to the present, covering a thirty year period that has just seen the appearance of the first issue of a journal devoted to this subject, namely the Journal of Random Structures & Algorithms. Necessarily our treatment is sketchy but we mention some of the outstanding results, applications and methods discovered during this time. Although the area has been nicely developed, it is still only a beginning for the theory of random graphs. We conclude with several unsolved problems including some that involve the Reconstruction Conjecture Isomorphism Problem Chromatic Number Hamiltonian Cycles.